The Effectiveness Of The Family Hope Program (PKH) In Reducing The Poverty Rate In Sei Bilah Village, Sei Lepan District, Langkat Regency - Khairina Khairina; Rahmad Sembiring; Suhendi Suhendi (Universitas Dehasen Bengkulu, 2026)
This qualitative study examines the effectiveness of Indonesia's Family Hope Program (Program Keluarga Harapan/PKH), a conditional cash transfer program, in reducing poverty in Sei Bilah Village, Sei Lepan District, Langkat Regency. The research is motivated by a paradoxical phenomenon: despite a 108.1% increase in PKH recipients (from 234 to 487 beneficiary families) and an 85.2% increase in benefit amounts (from IDR 1,890,000 to IDR 3,500,000 per year) during 2015-2024, the poverty rate only decreased by 1.4 percentage points (from 14.2% to 12.8%) and has stagnated at 12.8-12.9% since 2021. This study aims to explore and understand: (1) the processes, mechanisms, and obstacles in PKH implementation; (2) beneficiary families' experiences, perceptions, and utilization patterns of assistance; and (3) the strategies and effectiveness of PKH facilitation in promoting behavioral change and economic independence. The research employs an interpretive qualitative approach. Data were collected through in-depth interviews with 12 purposively selected informants comprising 8 beneficiary families, 2 PKH facilitators, and 2 village officials, complemented by field observations and documentation studies. Data were analyzed using Miles and Huberman's interactive analysis model involving data reduction, presentation, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings reveal that: (1) PKH implementation faces six structural obstacles: significant targeting errors (25-30% inclusion error due to outdated DTKS data), limited geographic access to disbursement locations imposing high transportation costs (4-5% of benefit amount), disproportionate facilitator workload (1:243-244 ratio exceeding the ideal 1:200), suboptimal inter-agency coordination for conditionality verification, limited basic service infrastructure (minimal health facilities, no senior high school, poor road conditions), and constrained facilitator authority to address structural poverty causes. PKH facilitators as street-level bureaucrats employ substantial discretion to bridge gaps between formal policies and local realities; (2) While all beneficiaries acknowledge PKH provides short-term safety net benefits, most remain skeptical about transformative impacts. Benefit utilization is dominated by basic needs consumption (70-80%), with limited allocation to education (15-20%) and productive investments (<5%). Conditionalities are perceived as fair but impose high opportunity costs; (3) Facilitation effectively increases short-term compliance with conditionalities but proves less effective in transforming long-term mindsets and fails to promote economic independence due to capacity limitations, inadequate incentives, and absence of complementary programs. This study concludes that PKH remains ineffective in reducing poverty in Sei Bilah Village due to five interrelated factors: targeting errors misallocating resources, inadequacy of benefits insufficient to fundamentally change household economic behavior, supply-side limitations in service quality and accessibility, structural poverty traps characterized by absence of formal employment opportunities preventing educated youth from escaping poverty, and limited grassroots implementation capacity. PKH functions primarily as a safety net preventing further impoverishment rather than as a springboard promoting upward economic mobility. These findings confirm street-level bureaucracy theory (Lipsky, 1980; 2010) regarding the crucial role of discretion in policy implementation, policy implementation theory (Edwards III, 1980) on the importance of communication, resources, disposition, and bureaucratic structure, and multidimensional poverty theory (Alkire & Foster, 2011; Sen, 1999) on the limitations of monetary approaches in addressing structural, multidimensional poverty. Policy recommendations include: (1) targeting system reform employing hybrid approaches combining proxy means test with community verification and more responsive data updating mechanisms; (2) benefit amount differentiation based on poverty severity and regional cost of living to ensure adequacy; (3) improved facilitator-beneficiary ratios (maximum 1:200) and enhanced facilitator incentives (minimum IDR 2-2.5 million monthly plus operational allowances); (4) PKH integration with complementary programs including skills training matching local labor market demands, microenterprise capital access, and graduation approaches facilitating transition from dependency to economic independence; (5) basic service infrastructure improvements including road rehabilitation, health facility strengthening, and senior high school establishment; and (6) local economic development creating formal employment opportunities for educated graduates through investment incentives and sector development strategies.